2009
DOI: 10.1073/pnas.0900044106
|View full text |Cite
|
Sign up to set email alerts
|

The phage λ major tail protein structure reveals a common evolution for long-tailed phages and the type VI bacterial secretion system

Abstract: Most bacteriophages possess long tails, which serve as the conduit for genome delivery. We report the solution structure of the N-terminal domain of gpV, the protein comprising the major portion of the noncontractile phage tail tube. This structure is very similar to a previously solved tail tube protein from a contractile-tailed phage, providing the first direct evidence of an evolutionary connection between these 2 distinct types of phage tails. A remarkable structural similarity is also seen to Hcp1, a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
278
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(290 citation statements)
references
References 34 publications
9
278
1
2
Order By: Relevance
“…In phage , the MTP (gpV) counts 246 amino acids. The N-terminal domain (gpV N 1-159) forms the MTP rings (64), while residues 160 to 246 (gpV C ) belong to an Ig-like domain, probably involved with host cell wall saccharide interactions (63). In SPP1, the MTP-coding gene (orf17.1) is subject to a frameshift alternative reading, leading either to an MTP of 159 residues, the core, or to a longer form of 266 residues (62).…”
Section: Discussionmentioning
confidence: 99%
“…In phage , the MTP (gpV) counts 246 amino acids. The N-terminal domain (gpV N 1-159) forms the MTP rings (64), while residues 160 to 246 (gpV C ) belong to an Ig-like domain, probably involved with host cell wall saccharide interactions (63). In SPP1, the MTP-coding gene (orf17.1) is subject to a frameshift alternative reading, leading either to an MTP of 159 residues, the core, or to a longer form of 266 residues (62).…”
Section: Discussionmentioning
confidence: 99%
“…An additional type of protein secretion system involved in protein translocation, known as a T6SS, has been found to contribute to interactions between bacteria and both bacteria and eukaryotic cells, including unicellular and multicellular eukaryotes (47). This system employs an assortment of membrane-associated proteins in order to coordinate the localization and assembly of the system; however, the secretory apparatus itself is composed of proteins that are structurally analogous to that of an inverted contractile bacteriophage tail (1,29,39). This coordinated contractile tail is utilized to deliver effector proteins to targets including the actin cytoskeleton in eukaryotic cells and peptidoglycan in bacterial cells (41,45).…”
mentioning
confidence: 99%
“…After their initial report, a number of bioinformatics-based comparative analyses of the T6SS gene clusters between bacterial strains have been made to assess possible function (4)(5)(6)(7)(8)(9)(10). In this issue of PNAS, both Leiman et al (11) and Pell et al (12) use structure-based analysis to demonstrate the existence of a structure/function relationship between the molecular components of T6SS and the tail proteins of bacteriophages T4 (11) and (12).…”
mentioning
confidence: 99%
“…Leiman et al (11) have also found that the structure of the hexameric ring formed by Hcp protein (14) is similar to the gp27 trimer and that the sequences of at least 2 T6SS proteins are highly similar to the T4 phage tail components (baseplate protein gp25 and the tail tube protein gp19). In the article by Pell et al (12) they demonstrate a strong similarity between a phage major tail protein and the Hcp protein of the T6SS. They carried out NMR-based determination of the structure of the N-terminal 153 residues of gpV major tail protein from phage followed by subsequent comparison with both monomeric and hexameric structure of the Hcp protein.…”
mentioning
confidence: 99%
See 1 more Smart Citation